2020
DOI: 10.1002/ejoc.201901660
|View full text |Cite
|
Sign up to set email alerts
|

Phenysilane and Silicon Tetraacetate: Versatile Promotors for Amide Synthesis

Abstract: Phenylsilane was reevaluated as a useful coupling reagent for amide synthesis. At room temperature, a wide range of amides and peptides were obtained in good to excellent yields (up to 99%). For the first time, Weinreb amides synthesis mediated by a hydrosilane were also documented. Comparative experiments with various acetoxysilanes suggested the involvement of a phenyltriacyloxysilane. From this mechanistic study, silicon tetracetate was shown as an efficient amine acylating agent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 55 publications
1
34
0
Order By: Relevance
“…1A) our reaction design (Fig. 1B) is based upon the dual reactivity of hydrosilanes, which mediate direct amide coupling [23][24][25][26] and amide reduction in the presence of a metal catalyst. [27][28][29][30] Combining these processes gives a reductive amination reaction in which carbon-nitrogen bond formation is complete before reduction begins, thereby avoiding unwanted reduction of the carboxylic acid, leading to alcohol by-products.…”
Section: Resultsmentioning
confidence: 99%
“…1A) our reaction design (Fig. 1B) is based upon the dual reactivity of hydrosilanes, which mediate direct amide coupling [23][24][25][26] and amide reduction in the presence of a metal catalyst. [27][28][29][30] Combining these processes gives a reductive amination reaction in which carbon-nitrogen bond formation is complete before reduction begins, thereby avoiding unwanted reduction of the carboxylic acid, leading to alcohol by-products.…”
Section: Resultsmentioning
confidence: 99%
“…Blanchet et al screened a series of commercially available silyl acetates: Me 2 Si(OAc) 2 (SR27), MeSi(OAc) 3 (SR28), Si(OAc) 4 (SR29), to determine their ability to acetylate morpholine stoichiometrically. 26 The results showed that the Si(OAc) 4 provided complete conversion to 4-acetylmorpholine after only 10 minutes at 0°C in tetrahydrofuran solvent. However, after 5 h MeSi(OAc) 3 provided only 57% yield and Me 2 Si(OAc) 2 gave no conversion.…”
Section: Silicon Tetraacetatementioning
confidence: 97%
“…In 2020 Blanchet et al re-examined the use of PhSiH 3 (SR11) and confirmed its utility for the formation of amides when using acetonitrile as the reaction solvent. 26 In contrast to Scheme 1 (A) Selected examples of SiCl 4 (SR1) mediated amide bond formation. 18 Reaction conditions: a 25°C, 10 h; b reflux, 1 h. (B) Selected examples of SiCl 4 mediated formation of dipeptides.…”
Section: Phenylsilanementioning
confidence: 99%
See 1 more Smart Citation
“…56 Recently, carboxylic acids were coupled with (CH 3 O) NHCH 3 ÁHCl using phenylsilane as a useful coupling agent in the presence of Et 3 N in 1,2-dichloroethane. The carboxylic acids appeared to couple with phenylsilane to generate 57 In the case of 2-methoxybenzoic acid, the reaction proceeded sluggishly due to electronic and steric factors to give N-methoxy-N-methyl 2-methoxybenzamide in 26% yield. Alternatively, α-hydroxycarboxylic acids underwent dehydrative amidation with N,O-dimethylhydroxylamine using biphenyl-based diboronic acid anhydride (DBAA, 67) in 1,2-dichloroethane to give the corresponding N-methoxy-N-methylamides.…”
Section: Preparation From Actived Amidesmentioning
confidence: 99%